Transboundary diseases of animals: Concerns and management strategies - Islam, M Ariful (Research in Agriculture Livestock and Fisheries, 2016)
Transboundary animal diseases (TADs) are greatly contagious epidemic diseases that can spread very rapidly, irrespective of national borders. They cause high rates of death and disease in animals, thereby having serious socio-economic and sometimes public health consequences while constituting a steady threat to the livelihoods of livestock farmers. With the development of technology, livestock production has gained an integral position in the national economy, socioeconomic development, poverty alleviation and nutrition supply for human. Livestock farming is one of the important sources of livelihood to rural peoples in Bangladesh. A healthy livestock is pleasure of any country including Bangladesh. However, rapid trend of globalization has brought upon challenges in maintaining healthy herds of livestock. The emerging infections of foreign origin could spread across national geographical borders and cause devastation in livestock population. As a result, there will be an emergence and spread of new disease in the region which was once free from the disease. Regional and international approaches have to be followed, and the FAO and OIE Global framework-TADs initiative provides the suitable concepts and objectives as well as an organizational framework to link international and regional organizations at the service of their countries to better prevent and control the risks on animal and human health and the economic impact of TADs and emerging animal diseases. In this paper, we have summarized the main diseases of livestock that are transboundary in nature, and sum up the challenges and necessary management strategies in controlling the transboundary diseases. Res. Agric., Livest. Fish.3(1): 121-126, April 2016